Comparable dose estimates of blinded whole blood samples are obtained independently of culture conditions and analytical approaches. Second RENEB gene expression study. (2nd January 2017) - Manning, Grainne; Macaeva, Ellina; Majewski, Matthaeus; Kriehuber, Ralf; Brzóska, Kamil; Abend, Michael; Doucha-Senf, Sven; Oskamp, Dominik; Strunz, Sonja; Quintens, Roel; Port, Matthias; Badie, Christophe
Abstract: Purpose: This collaboration of five established European gene expression labs investigated the potential impact of culture conditions on the transcriptional response of peripheral blood to radiation exposure. Materials and methods: Blood from one healthy donor was exposed ex vivo to a Cobalt 60 source to produce a calibration curve in addition to four unknown doses. After exposure, the blood samples were either diluted with RPMI medium or left untouched. After 24-h incubation at 37 °C the diluted blood samples were lysed, while the undiluted samples were mixed with the preservative RNALater and all samples were shipped frozen to the participating labs. Samples were processed by each lab using microarray (one lab) and QRT-PCR (four labs). Results: We show that although culture conditions affect the total amount of RNA recovered ( p  < .0001) and its integrity ( p  < .0001), it does not significantly affect dose estimates (except for the true dose at 1.1 Gy). Most importantly, the different analysis approaches provide comparable mean absolute difference of estimated doses relative to the true doses ( p  = .9) and number of out of range (>0.5 Gy) measurements ( p  = .6). Conclusion: This study confirms the robustness of gene expression as a method for biological dosimetry.